Accuracy and retention of denture base fabricated by heat curing and additive manufacturing. Issue 1 (January 2019) - Tasaka, Akinori; Matsunaga, Satoru; Odaka, Kento; Ishizaki, Ken; Ueda, Takayuki; Abe, Shinich; Yoshinari, Masao; Yamashita, Shuichiro; Sakurai, Kaoru
Abstract: Purpose: The aim of the present study was to compare the accuracy and retentive force of an experimental denture base fabricated using additive manufacturing and heat curing. Methods: A maxillary edentulous jaw model made of silicon was used. The shape data for the working cast and wax pattern of the experimental denture base were obtained using a dental laboratory scanner. Fabrication of the experimental denture bases was performed using heat curing and additive manufacturing. The shape data for the experimental denture bases was captured using an optical scanner. The shapes of the two experimental denture bases were compared with the shape of the working cast. A digital force gauge was used to measure the traction force. Pulling was maintained until the experimental denture base separated from the elastic model. Retention was set as the maximum value for the traction force. In order to compare the retentive force of the two experimental denture bases. Results: The experimental denture base fabricated using additive manufacturing was more accurate than the experimental denture base fabricated using heat curing. The experimental denture base fabricated using additive manufacturing demonstrated greater retentive force than the experimental denture base fabricated using heat curing. Conclusions: In this study, the experimental denture base fabricated using additive manufacturing was more accurate and obtained greater retentive force than the experimental denture base fabricated using heat curing.